Peran Kecerdasan Emosional dalam Membentuk Perilaku Anti-Bullying Siswa: Studi Kasus Kualitatif di SMPK Rosa Mystika Liliba - Maria Orlandi Kehi; Rikardus Herak (Edu Berkah Khatulistiwa, 2026)
This qualitative case study explores the role of emotional intelligence in shaping students' anti-bullying behavior within the bounded context of SMPK Rosa Mystika, Liliba. The informants included ninth-grade students, a guidance and counseling teacher, and a homeroom teacher. Data were collected through semi-structured interviews, school-environment observations, documentation of anti-bullying programs, and field notes. The data were analyzed using Braun and Clarke's six-phase thematic analysis: familiarization, initial coding, theme generation, theme review, theme definition and naming, and report writing. Trustworthiness was strengthened through source and technique triangulation. The findings indicate that emotional intelligence was reflected in students' ability to recognize emotions, regulate responses during conflict, empathize with victims, and take action by reprimanding, assisting, or reporting harmful behavior. A school culture emphasizing mutual respect, teacher guidance, counseling services, anti-bullying socialization, posters, videos, drama activities, and morning literacy supported these behaviors. However, formal standard operating procedures, case documentation, and systematic reporting mechanisms still require strengthening. The study concludes that emotional intelligence contributes to anti-bullying behavior when supported by a psychologically safe and responsive school climate.